STUDI KASUS PERAN KPID DIY DALAM MENANGANI PELANGGARAN BAHASA NONVERBAL DAN ADEGAN SEKSUAL PADA ANTV DAN ADITV MENURUT PEDOMAN PERILAKU PENYIARAN DAN STANDAR PROGRAM SIARAN (P3SPS) - Handayani, Veronika Suci; Anwar, Rofiq (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
Television broadcasting has an important role in conveying messages, entertainment and education to the public. However, with advances in technology and media freedom, the problem of violations in television broadcasting is increasingly complex. KPID DIY seeks to establish cooperation to advance broadcasting institutions in the Special Region of Yogyakarta in accordance with Regional Regulation Number 13 of 2016. This research aims to investigate the role of KPID DIY in handling violations and identifying the effectiveness of disciplinary action against television stations that violate P3SPS guidelines. The research method used is qualitative with a case study approach, focusing on violations and sanctions from KPID DIY. The research results show that violations committed by ANTV and Aditv, including the use of harsh language and sexual scenes, were handled the same way. KPID DIY carries out P3SPS outreach and provides administrative sanctions for violators. Broadcast programs relating to sexuality are strictly regulated, they may only be broadcast on the D classification schedule, while programs for children are regulated on the P classification schedule with clear provisions regarding appropriate content.